1991
DOI: 10.7589/0090-3558-27.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and Serum Chemistry of Cottontail Rabbits of Southern Illinois

Abstract: In 1983 and 1984 blood was collected from 79 cottontail rabbits (Sylvilagus floridanus) confined to an outdoor enclosure in southern Illinois to establish reference values for hematology and serum chemistry. Packed cell volume, sodium, potassium, chloride, glucose, calcium, carbon dioxide, blood urea nitrogen, creatinine, uric acid, cholesterol, albumin, bilirubin, alkaline phosphatase, aspartate transaminase, alanine aminotransaminase, total protein, albumin/globulin ratio, and osmolality were measured. Sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
5
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 3 publications
6
16
5
3
Order By: Relevance
“…Our values for total proteins in the serum of rabbits from all the groups were similar to the those found in healthy rabbits by Yu et al (1979), Scheunert and Trautmann (1987), Bortolotti et al (1989) and Lepitzki and Woolf (1991). Our relative values of the quantity of albumin in the serum of rabbits of all groups involved in the experiment were similar to the values quoted as physiological in rabbits by Irfan (1967Irfan ( ), Y u et al (1979 and Scheunert and Trautmann (1987), while they are higher than those given for healthy rabbits by Lepitzki and Woolf (1991).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our values for total proteins in the serum of rabbits from all the groups were similar to the those found in healthy rabbits by Yu et al (1979), Scheunert and Trautmann (1987), Bortolotti et al (1989) and Lepitzki and Woolf (1991). Our relative values of the quantity of albumin in the serum of rabbits of all groups involved in the experiment were similar to the values quoted as physiological in rabbits by Irfan (1967Irfan ( ), Y u et al (1979 and Scheunert and Trautmann (1987), while they are higher than those given for healthy rabbits by Lepitzki and Woolf (1991).…”
Section: Discussionsupporting
confidence: 73%
“…Our relative values of the quantity of albumin in the serum of rabbits of all groups involved in the experiment were similar to the values quoted as physiological in rabbits by Irfan (1967Irfan ( ), Y u et al (1979 and Scheunert and Trautmann (1987), while they are higher than those given for healthy rabbits by Lepitzki and Woolf (1991).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…They are higher than the values reported by Friedel and Mattenheimer (1970), Schievelbein et al (1970), Grötsch and Hajdu (1971), Dabew et al (1976), Lindena and Traut-schold (1986) and Liker et al (1998), but lower than those found by Lepitzki and Woolf (1991). The slightly higher AST and ALT values of rabbits included in this experiment were due to the slight haemolysis that occurred during the taking of blood samples, rather than to the nutritive influence of dehydrated olive cake pulp added to the feed.…”
Section: Discussioncontrasting
confidence: 52%